Pelaksanaan Empowerment Dapat Meningkatkan Kinerja Perusahaan - Andriansyah Saputra (Jurnal Strategi Bisnis Teknologi, 2024)
With empowerment conditions that can be seen from the four dimensions, namely meaning, competence, self-determination, impact, job satisfaction will be created which will then have an impact on company performance. In the property sector, decisions on project work take into account the correctness of the information, certainty of payment methods and profit margins that are appropriate to the level of project difficulty. Employees' skills and abilities in negotiating, planning, being keen to see opportunities and making decisions in the project process from start to finish are always needed to counter changes and environmental influences that will inevitably occur in the project work process. The success of a project work can be seen from the company's performance which is based on the completion of a project according to or faster than schedule and conformity to the detailed project specifications agreed with the project owner.